Comparison of methods for detecting asymptomatic malaria infections in the China–Myanmar border area - Yonghong Zhao (Malaria Journal, 2017)
Abstract Background Sensitive methods for detecting asymptomatic malaria infections are essential for identifying potential transmission reservoirs and obtaining an accurate assessment of malaria epidemiology in low-endemicity areas aiming to eliminate malaria. PCR techniques to detect parasite nucleic acids (DNA or RNA) are among the most commonly used molecular methods. However, most of these methods are of low throughput and cannot be used for large-scale molecular epidemiological studies. A recently developed capture and ligation probe-PCR (CLIP-PCR) is claimed to have the sensitivity of molecular techniques and the high throughput capacity needed for screening purposes. This study aimed to compare several molecular methods for detecting asymptomatic and submicroscopic Plasmodium infections in healthy residents of a malaria-hypoendemic region in Southeast Asia, where malaria elimination is in sight. Method This study compared three molecular detection methods side-by-side, namely nested PCR targeting the rRNA genes, nested RT-PCR to detect parasite rRNA, and CLIP-PCR to detect parasite rRNA in 1005 healthy individuals in northeastern Myanmar. For nested PCR and RT-PCR, parasite DNA and total RNA were extracted from ~100 µL of blood, whereas RNA used for CLIP-PCR was from a 3 mm disk of dried blood filter paper. The sensitivity and specificity of these methods were compared with those of conventional light microscopy. In addition, RT-PCR and quantitative RT-PCR (qRT-PCR) targeting the Pvs25 gene in Plasmodium vivax were used to assess gametocyte prevalence in the samples. Results Light microscopy detected Plasmodium infections in only 1.19% of the residents harbouring the parasites. CLIP-PCR had slightly better performance and detected Plasmodium infections in 1.89% of the population. Further improvement was achieved by nested PCR to detect parasite DNA, which detected P. vivax and Plasmodium falciparum infections in 2.39% of the residents. The nested RT-PCR targeting rRNA, however, detected as many as 187 (18.61%) individuals having Plasmodium infections with P. vivax being the predominant species (176 P. vivax, 5 P. falciparum and 6 P. falciparum/P. vivax mixed infections). Of the 210 Plasmodium-positive samples detected by all molecular methods, 115 were Pvs25-positive by qRT-PCR, indicating that a large proportion of asymptomatic individuals were gametocyte carriers. Conclusion Nested RT-PCR based on the detection of asexual-stage parasite rRNA was the most sensitive, with a more than sixfold higher sensitivity than the other two molecular methods of parasite detection. CLIP-PCR has an increased throughput, but its sensitivity in this study was much lower than those of other molecular methods, which may be partially due to the smaller amount of RNA input used.